2010
DOI: 10.1080/13803390903468863
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functioning in postpartum depressed versus nondepressed females and nonpostpartum controls

Abstract: We compared 21 postpartum depressed (PPD) women, 22 postpartum nondepressed (PPND) women, and 24 nondepressed, nonpostpartum women on a neuropsychological test battery. Postpartum women presented lower performance on initial learning (Rey Auditory Verbal Learning Test, RAVLT) than did controls. Further, PPD women presented lower performance on Part B of the Trail Making Test than did PPND women and controls. No differences were observed in RAVLT recall or recognition trials, in Greek versions of the Controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…A handful of studies using neuropsychological measures have found evidence of impaired executive function associated with postnatal depression. For example, Pio de Almeida, Jansen, Köhler, Pinheiro, da Silva (2012) report evidence of impaired working and short-term memory in depressed parents; Messinis et al. (2010) report poorer performance on a learning task and an attention switching task by postnatally depressed women compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of studies using neuropsychological measures have found evidence of impaired executive function associated with postnatal depression. For example, Pio de Almeida, Jansen, Köhler, Pinheiro, da Silva (2012) report evidence of impaired working and short-term memory in depressed parents; Messinis et al. (2010) report poorer performance on a learning task and an attention switching task by postnatally depressed women compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…La diferencia que se pudo establecer entre el embarazo y el puerperio, fue que esta etapa además del déficit de memoria se caracteriza por la presencia lentitud en el procesamiento de la información. Messinis et al 20 examinaron el funcionamiento cognitivo en puérperas con…”
Section: Caracterización Cognitiva Del Período Postpartounclassified